2021
DOI: 10.5194/hess-25-4259-2021
|View full text |Cite
|
Sign up to set email alerts
|

Plant hydraulic transport controls transpiration sensitivity to soil water stress

Abstract: Abstract. Plant transpiration downregulation in the presence of soil water stress is a critical mechanism for predicting global water, carbon, and energy cycles. Currently, many terrestrial biosphere models (TBMs) represent this mechanism with an empirical correction function (β) of soil moisture – a convenient approach that can produce large prediction uncertainties. To reduce this uncertainty, TBMs have increasingly incorporated physically based plant hydraulic models (PHMs). However, PHMs introduce addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…Here, we have demonstrated that PHM hydraulic parameters can be inferred at the individual level using a MCMC inversion approach using measured sap flow. Reliable and simultaneous inference of multiple hydraulic model parameters has great potential to assist model parametrization, which remains a major impediment to the adoption of PHMs (Feng, 2020; Paschalis et al., 2020; Sloan et al., 2021). The inferred hydraulic traits—including the whole‐plant effective embolism vulnerability and maximum xylem conductance—are subject to a number of uncertainties related to model structure and input data availability but capture well the inter and intra‐specific variability in plant water use and hydraulic vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we have demonstrated that PHM hydraulic parameters can be inferred at the individual level using a MCMC inversion approach using measured sap flow. Reliable and simultaneous inference of multiple hydraulic model parameters has great potential to assist model parametrization, which remains a major impediment to the adoption of PHMs (Feng, 2020; Paschalis et al., 2020; Sloan et al., 2021). The inferred hydraulic traits—including the whole‐plant effective embolism vulnerability and maximum xylem conductance—are subject to a number of uncertainties related to model structure and input data availability but capture well the inter and intra‐specific variability in plant water use and hydraulic vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…The recent implementations of PHMs into terrestrial biosphere models have shown promising corrections of previous prediction biases in gross primary productivity and evapotranspiration (Bonan et al., 2014; Eller et al., 2020; Kennedy et al., 2019; L. Li et al., 2021; Powell et al., 2013; Sabot et al., 2020; Xu et al., 2016) as well as soil water balance (Kennedy et al., 2019), especially under drought conditions. However, the use of PHMs in models is still hindered by the need to acquire plant hydraulic traits for parameterization (Feng, 2020; Paschalis et al., 2020; Sloan et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in transpiration during drying is often included in soil-plant-atmosphere models through a piecewise linear function, representing water-stress-induced reductions in E (Federer, 1979;Sloan et al, 2021). These observations motivate the inclusion of a further constraint in the optimization relative to OPT1 and OPT2, in the form of a soil-moisturelimited transpiration rate under dry conditions that effectively constrains the allowable range of stomatal conductance (Manzoni et al, 2013),…”
Section: B2 Derivation Of Opt3: Dynamic Feedback Optimization With Tr...mentioning
confidence: 99%
“…A n , and consequently T , can be limited by many external factors such as PAR, vapor pressure deficit, atmospheric pressure, soil moisture, and air temperature (Sloan et al, 2021;Cong et al, 2022). Under no external limitations, vegetation transpires as much as its physiology allows.…”
Section: Daily Dynamicsmentioning
confidence: 99%